Health-promoting lifestyle among children of parents deceased versus healed from cancer in Shiraz, Iran - Alamdarloo, Ghorban Hemati; Nemati, Shahrooz; Padervand, Hafez; Nazari, Zahra; Amiri, Parvin (Penerbit Universiti Kebangsaan Malaysia, 2024)
The impact of cancer is not limited to the patient but also affects the life of the patient's spouse, children, family members, and friends. The present study aimed to compare the health-promoting lifestyle in children of parents deceased from cancer and children of parents healed from cancer. The sample consisted of 115 people (58 children of parents healed from cancer and 57 children of parents deceased from cancer) in Shiraz, Iran. The Health-Promoting Lifestyle Profile II (HPLP II) was used to measure different types of health-promoting lifestyles (health responsibility, physical activity, nutrition, spiritual growth, interpersonal relations, and stress management). The collected data were analysed using a multivariate analysis of variance. The results showed that the children of parents healed from cancer significantly achieved higher scores in spiritual growth, responsibility in health, stress management, physical activity, and nutrition than children of parents deceased from cancer. Moreover, the results showed no significant difference between the two groups in interpersonal relations. This study highlighted the importance of a health-promoting lifestyle in families with a cancer parent.